1980
DOI: 10.1159/000123058
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Adrenal Stress Responsiveness in the Rat

Abstract: Serum and adrenal corticosterone was measured by competitive protein-binding radioassay in rats subjected to saline injection, ACTH administration or ether fumes. Groups of rats were tested at 5, 7, 9, 11, 13, 15, 20 and 25 days of age and measurement of hormone level was made either before treatment, to obtain basal values, or 15 min after treatment. Furthermore, the time-course of corticosterone release after ether was determined in 9- and 15-day-old rats. Neonatal rats responded to ether exposure, ACTH admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 16 publications
7
49
0
1
Order By: Relevance
“…Manin and DeLost (24) demonstrated that neurotrophic stress increased MCR through increased Vd in the conscious guinea pig. Given the developmental increase in the stress response in the rat (1,25), similar effects on MCR and Vd would result in a pattern of response opposite to that seen in Figure I. Finally, Herbst et al (26) showed that repeated anesthesia in adult rats had no effect on in vitro reduction of ring A of corticosterone.…”
Section: Discussionmentioning
confidence: 93%
“…Manin and DeLost (24) demonstrated that neurotrophic stress increased MCR through increased Vd in the conscious guinea pig. Given the developmental increase in the stress response in the rat (1,25), similar effects on MCR and Vd would result in a pattern of response opposite to that seen in Figure I. Finally, Herbst et al (26) showed that repeated anesthesia in adult rats had no effect on in vitro reduction of ring A of corticosterone.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, peak levels of BrdU-labeled cells in the dentate gyrus occur between P9-11 (Liu et al 2003) and P11 is the day at the beginning of the critical period for MA-induced long-term cognitive deficits (Vorhees et al 1994Williams et al 2002Williams et al , 2003bWilliams et al ,c, 2004b. Similar to the effects of MA, other factors such as corticotropin-releasing factor (Walker et al 1986) or various stressors (Schoenfeld et al 1980) administered during the neonatal period can be described as producing a U-shaped curve response pattern of corticosterone release. In the current study we also demonstrated this Ushaped corticosterone response to MA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, basal circulating corticosterone levels are very low and mild stressors are unable to induce a peripheral corticosterone response (Levine et al 2000). However, a variety of severe or prolonged stressors disrupt the quiescence of the hypothalamic-pituitary-adrenal (HPA) axis during this time of development (Schoenfeld et al 1980, Walker et al 1991, Yi & Baram 1994. The high levels of circulating corticosterone induced by these treatments are usually seen as the cause for a consequently altered developmental trajectory and finally persistent consequences in the adult animal.…”
Section: Introductionmentioning
confidence: 99%